Preoperative Ultrasonography as a Predictor of Difficult Laparoscopic Cholecystectomy - Kumar, Rajender (Asian Journal of Medical Radiological Research, 2017)
Introduction: The most regularly done major abdominal treatment worldwide is laparoscopic cholecystectomy, which has quickly become the method of choice for routine gallbladder removal. The purpose of this study was to explore if preoperative ultrasonography could be used to predict whether or not a laparoscopic cholecystectomy would be difficult. Subjects and Methods: 78 patients with cholelithiasis were recruited from the World College of Medical Sciences Research and Hospital’s surgical OPD and underwent elective laparoscopic cholecystectomy if they met all of the study’s inclusion and exclusion criteria. Results: There were 78 instances analysed in all, with 22 cases (28.2%) being man and 56 cases (71.8%) being females. Twenty-five of the seventy-eight laparoscopic cholecystectomy operations (32.1 percent) were challenging. Gall bladder adhesions, difficult Calot dissection, leakage of bile and stones, bleeding obstructing vision, aberrant biliary tree anatomy, and intra-hepatic gall bladder were found in 94.6 percent and 89.4 percent of the 25 difficult laparoscopic cholecystectomy surgeries, respectively. Conclusion: The preoperative ultrasonography results of gallbladder wall thickness, pericholecystic collection, quantity of gall stones, impacted stones in gall bladder, and gall bladder transverse diameter can all be used to predict difficult laparoscopic cholecystectomy. The best modality for diagnosing gall stones is ultrasound, however it is operator-dependent. To obtain high-quality images and establish correct diagnoses, a high level of competence and experience is required.